Verbal and Non-Verbal Communication of Nurses and Its Relationship with Patient Satisfaction: A Study at Mega Buana Hospital, Palopo, 2025 - Musdalifah; Sastria, Andi; Supri, Aisyah; Papayungan, Sutrisno (Althar Cendikia Education, 2025)
One of the major issues in nursing services, both in Indonesia and globally, is the lack of effective verbal and non-verbal communication by nurses, which can significantly impact patient satisfaction. Patient dissatisfaction can affect the development of nursing services and the overall quality of hospital care. Nurses’ communication skills are essential in providing care, as they influence the patient's perception of service quality. This study aimed to examine the relationship between nurses’ verbal and non-verbal communication and patient satisfaction in the inpatient ward of Mega Buana Hospital, Palopo. An observational study with a cross-sectional design was used. A total of 83 respondents were selected using purposive sampling. Data were collected through questionnaires and observation sheets. The data were analyzed using the Chi-Square test. The results showed a significant relationship between verbal communication and patient satisfaction (p-value = 0.012 < α = 0.05), and between non-verbal communication and patient satisfaction (p-value = 0.018 < α = 0.05). It can be concluded that most nurses demonstrated effective verbal and non-verbal communication, and most patients reported being satisfied with the services received. This study confirms that therapeutic communication by nurses plays a vital role in influencing patient satisfaction in the inpatient setting at Mega Buana Hospital, Palopo.